UPAYA MENCIPTAKAN CUSTOMER DELIGHT MELALUI SERVICE EXCELLENCE HOTEL SANTIKA SILIGITA NUSA DUA BALI (Survei terhadap Tamu SIP Member yang Menginap di Hotel Santika Siligita Nusa Dua Bali) - Sari, Norma Komala; Wibowo, Lili Adi; Ridwanudin, Oce (THE Journal : Tourism and Hospitality Essentials Journal, 2014)
The purpose of this research are to findings regarding the implementation of service excellence, customer delight, and effect of service excellence towards customer delight in Hotel Santika Siligita Nusa Dua Bali. Using 100 respondents from SIP member guests who stay in the Hotel Santika Siligita Nusa Dua Bali, who collect from systematic random sampling and calculated by simple linear regression. The results showed that the service excellence has a significant influence on customer delight in Hotel Santika Siligita Nusa Dua Bali.